Primary malignant cutaneous lymphomas excluding mycosis fungoides. Anatomoclinical study of 16 cases - Wechsler, J; Caillaud, J M; Clerici, T; Ghozali, F; Micheau, C; Pinaudeau, Y (Annales de pathologie, 1984)
Cutaneous primary lymphomas excluding mycosis fungoides and Sezary Syndrome represent a rare condition. Few papers are published on the subject. The authors report a retrospective study of 16 cases concerning only these primary lymphomas. It comprises 10 adults and 6 children. In 13 cases the cutaneous tumor was solitary without extra-cutaneous lesion, in 3 cases there was a satellite simultaneous lymph node. The most frequent location was head and neck region (7 cases with 4 cases from children); limbs were concerned too (5 cases/16); more rarely trunk. Our cases were classified with reference to lennert's classification. We found that large cells lymphomas were predominant: centroblastic (4 cases), lymphoblastic (4 cases), immunoblastic lymphomas (6 cases). The clinical course was unfavourable in 50% of our cases in less than 3 years: 6 lethal cases, and 2 metastatic disseminations. These 8 cases belonged to the pejorative group of lymphomas (large cells type). The 2 cases with small cells population (centrocyto-centroblastic and lymphoplasmocytoïd type) were free of disease for 5 and 2 years after diagnosis. Thus, our experience suggests that there is a relations hip between the histologic type of cutaneous lymphoma and the course of the disease. In disseminated cases, the extra-cutaneous extension was located in lymph nodes, bone marrow, as it was mentioned in literature.